EFFECTS OF GERMINATION ECOLOGY ON IN VITRO GERMINATION PERFORMANCE OF HIGHLAND BAMBOO (Yushania alpina) SEED COLLECTED FROM KEFA, SOUTH WEST ETHIOPIA - Getnet Tesfaye, Belete; Mulatu Mengesha, Yigardu; Melese Birlie, Smegnew; Nigatu Gebeyehu, Marshet (Indonesian Journal of Forestry Research, 2022)
Yushania alpina is an African endemic bamboo species, and it is a valuable resource in ecological and socioeconomically value in Ethiopia. However, low germination is a challenge for seedlings production besides its seed availability is scarce. To improve the seed germination capacity, using different germination ecology treatments are needed. Hence, this study was initiated to investigate the effects of different germination ecology, and to determine the qualities, size, and yield of Y. alpina seed. The collected matured fruits were processed, and then the cleaned (pure) and not cleaned (impure) seed were used for this study. This study had two phases; the first was to measure the purity, moisture content, seed character, seed yield; and the second was to investigate the effects of different germination ecology for in vitro seed germination of Y. alpina using pure and impure seeds. In this result, the purity, moisture content, seed size, seed weight, and grain yield were determined for cleaned Y. alpina seed. The highest germination capacity (55%) of pure seed was recorded on T2 (paper + ambient temperature), followed by 38% on T1 (sand +ambient temperature), and 31% on T3 (paper + incubator (25°C)); however, these treatments produced lower results in the impure seed. Hence, this result concluded that using sand media at ambient temperature as germination ecology is preferred to enhance the germination capacity of Y. alpina seed. Also, seed surface disinfection using antifungals is recommended to reduce seed contamination.